Enhanced antioxidant properties as a function of selenium uptake by edible mushrooms cultivated on selenium-accumulated waste post-harvest wheat and paddy residues - Poonam Bhatia; Ranjana Prakash; N. Tejo Prakash (International Journal of Recycling of Organic Waste in Agriculture)
Background Majority of the post-harvest agri-residues from agricultural activity in Punjab, India, is burnt in the field resulting in the loss of soil fertility and release of large amounts of air pollutants. In an effort to reutilize the selenium-accumulated waste wheat and paddy straw from seleniferous region of Punjab, two varieties of edible mushrooms, Pleurotus sajor-kaju and Volvariella volvacea, were cultivated on Se-rich wheat and paddy straw, respectively. Results Se concentration in Se-enriched P. sajor-kaju and V. volvacea (43.5 ± 2.1 and 35.0 ± 1.1 lg/g) was significantly higher than control (5.2 ± 1.0 and 5.57 ± 0.07 lg/ g), respectively. The antioxidant activity as depicted by total phenol content, total oxidant activity, DPPH scavenging, metal chelation and lipid peroxidation inhibiting activity of extracts from Se-fortified mushrooms were significantly higher (p.05 to p.001) than control mushrooms. Conclusion The increased antioxidant activity is attributed to be induced by the accumulation of selenium by these species of mushrooms, indicating the antioxidant nature of selenium in biological systems. Further, the present study also demonstrates the use of Se accumulated agricultural residues as substrates for producing Se-rich mushrooms as potential sources for Se supplementation/ nutraceutical applications.